Beam acceleration through proton radio frequency quadrupole accelerator in BARC. (3rd May 2016) - Bhagwat, P.V.; Krishnagopal, S.; Mathew, J.V.; Singh, S.K.; Jain, P.; Rao, S.V.L.S.; Pande, M.; Kumar, R.; Roychowdhury, P.; Kelwani, H.; Rao, B.V. Rama; Gupta, S.K.; et al.
Abstract: A 3 MeV proton Radio Frequency Quadrupole (RFQ) accelerator has been designed at the Bhabha Atomic Research Centre, Mumbai, India, for the Low Energy High Intensity Proton Accelerator (LEHIPA) programme. The 352 MHz RFQ is built in 4 segments and in the first phase two segments of the LEHIPA RFQ were commissioned, accelerating a 50 keV, 1 mA pulsed proton beam from the ion source, to an energy of 1.24 MeV. The successful operation of the RFQ gave confidence in the physics understanding and technology development that have been achieved, and indicate that the road forward can now be traversed rather more quickly.